Using plastic pollution management worksheets in fundamental science class: An investigation on students’ sustainable awareness - Sukardi, Rendi Restiana; Ishak, Nor Asniza; Rachmania, Setyaningsih; Kurniawan, Dede Trie; Ananthia, Winti; Shidiq, Ari Syahidul; Meilinda, Meilinda; Ani, Neng (Education and Development Research, 2025)
Awareness among Indonesian society regarding plastic use and its management remains alarmingly low. This highlights an urgent need to strengthen sustainability education and responsible environmental practices. The implementation of the Plastic Pollution Management Worksheet uses a practicum-based method to foster greater sustainability awareness by integrating critical reflection and problem-solving strategies in addressing plastic pollution. This hands-on approach also encourages pro-environmental behavioural changes among learners. This study seeks to evaluate the impact of the Plastic Pollution Management Worksheet in practicum on students' sustainability awareness before and after its use. A one-group pre-test and post-test design was adopted, involving 40 university students, with a self-efficacy questionnaire used to assess five key indicators of sustainability awareness. The findings indicate that the implementation of practicum with the Plastic Pollution Management Worksheet had a moderate impact on enhancing students' sustainability awareness, with the most notable improvements observed in cognitive awareness (understanding sustainability concepts) and social engagement. Although improvements were noted across all dimensions, the development of sustainable behavioural changes requires further time and reinforcement. In conclusion, the practicum with Plastic Pollution Management Worksheet demonstrates potential as an innovative pedagogical strategy in sustainability education, though its effectiveness could be maximised by integrating it with other complementary educational approaches.